Dimethylsulfoxide (DMSO) clusters dataset: DFT relative energies, non-covalent interactions, and cartesian coordinates - Alhadji Malloum; Jeanet Conradie (Data in Brief, 2022)
Theoretical understanding of dimethylsulfoxide (DMSO) liquid depends on the understanding of the DMSO clusters. In this work, we provide the structures and the energetics of the DMSO clusters. The structures have been generated using ABCluster and further optimized at the MP2/aug-cc-pVDZ level of theory. The final structures have been optimized at two different levels of theory: PW6B95D3/aug-cc-pVDZ and ωB97XD/aug-cc-pVDZ. The Cartesian coordinates of the structures optimized at the MP2/aug-cc-pVDZ level of theory are also reported. The relative energies of the structures can be used to locate the most favorable structures of the DMSO clusters. The Cartesian coordinates of the structures can be used for further investigations on DMSO clusters. In addition, we report the data related to the quantum theory of atoms in molecule (QTAIM) analysis of the investigated clusters. The QTAIM data reported in this work can be used to understand and determine the nature of non-covalent interactions in DMSO clusters. For further reading and discussion on the data reported here, please report to the original manuscript Malloum and Conradie (2022) [1].